As estórias da casa velha da ponte e a formação de leitores literários na educação básica - Freire, Débora Cunha (2024)
This dissertation addresses the trajectory and developments of the research conducted during the Graduate Program in Teaching in Basic Education at the Center for Teaching and Applied Research in Education (CEPAE) of the Federal University of Goiás (UFG), and is part of the research line Theoretical-Methodological Conceptions and Teaching Practices. The study aimed to investigate the formation of the literary reader and aesthetic enjoyment through the reading of short stories and poems by Cora Coralina. For this purpose, the study corpus includes the short stories from the book As Estórias da Casa Velha da Ponte and other prose and verse works by the mentioned author. Based on this corpus, the following theoretical references, among others, were mobilized to reflect on the teaching of literature and the formation of readers: Antonio Candido (2000, 2002, 2004), Rildo Cosson (2006), Tzvetan Todorov (2007), Maria Teresa Andruetto (2017), Teresa Colomer (2014), Regina Zilberman (1991), Paulo Freire (1994, 1996, 1997), Pierre Bourdieu (1996), Italo Calvino (2009), and Ana Maria Machado (2002). The methodology of the work is Action Research, involving 8th-grade students from a municipal school in Goiânia. The general objective of this work is to investigate how students in the final years of elementary school experience aesthetic enjoyment in literary reading through workshops on reading short stories and poems by Cora Coralina. It was observed how these readings could be stimulating aesthetic experiences to develop a taste for literary appreciation, and whether the exploration of these textual genres could motivate students to read other texts of the same genres. The collaboration was significant, generating positive results regarding reading and writing literary texts, as the workshops allowed students to be the protagonists of their reading experiences and to develop creative and subjective productions such as memory texts, poems, and rewritings of short stories. Data analysis allowed for an understanding of the effectiveness of reading practices conducted in the classroom, identifying reading preferences and the enjoyment of literary texts by students. The Educational Product is an eBook titled "Between Pages and Bridges: The Magic of Stories in the Formation of Literary Readers in Basic Education," aimed at helping elementary school teachers promote literary reading among students in the final years, contributing to the formation of readers and offering practices to encourage enjoyment through the reading of short stories